STUDI KOMPARATIF KEUNTUNGAN PENGGUNAAN MESIN PEMIPIL JAGUNG BERKELOBOT DENGAN MESIN PEMIPIL JAGUNG TANPA KELOBOT DI DESA BANYU URIP KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Kurniadi, Denny; Afriyatna, Sisvaberti (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2015)
Study of Comparative Advantage Using corn sheller machine and without husk corn sheller machine Banyu Urip village Tanjung Lago Banyuasin regency district. This study aims to determine how the process of post-harvest uses corn sheller machine see with sheller machine without the husk and to find out how different benefit corn farmers who use the machine with sheller and sheller machine without husk Banyu UripIn the village of Tanjung Lago Banyuasin district. The method used was the method of survey of corn growers in the Banyu Urip village of Tanjung Lago Banyuasin District. Methods of sampling done by using disproportionate stratified random sampling by using two layers, wherein a layer of the first farmers who use the machine sheller as many as 16 farmers and layer II farmers who use the machine sheller without husk as many as 16 farmers in the sample. Data processing methods were interviews, data collected in this study include primary data and secondary data. Primary data obtained from respondents through direct interviews and field observations accompanied by a list of questions has been provided while the secondary data obtained from the authorized agency or institution related to this research. Data were processed using mathematical models and presented in the form of tabulation.The results showed that the process of postharvest maize includes a series of activities, namely harvesting, stripping, drying corn and loosen bean andto find out how different benefit corn farmers who use the machine sheller see with machine sheller without husk ie From the Test t count in the can that reject Ho means profit I significantly different layers with the advantage of this second layer means. Big advantage corn farmers who use the machine and the machine sheller without sheller see husk respectively by layer I was Rp 18,315,039 per hectare per season planting and layer II amounting to Rp 17,463,863 per hectare per season planting.